1999
DOI: 10.1080/00207284.1999.11490964
|View full text |Cite
|
Sign up to set email alerts
|

Attachment Style, Traumatic Bonding, and Developing Relational Capacities in a Long-Term Trauma Group for Women

Abstract: Adults with histories of severe childhood abuse often experience considerable difficulties with interpersonal trust. At the same time, they may strongly desire to be less alone with the painful aftereffects of their traumatic pasts. Psychotherapy groups have often been recommended as important components of treatment for reducing survivors' feelings of isolation and shame. We propose that an understanding of attachment styles and of traumatic bonding helps to clarify the specific manifestations of interpersona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…So far, individual therapy and group therapy seem to lead to fewer symptoms and better psychosocial functioning [93]. Psychotherapy groups have often been recommended to reduce the victim's feelings of isolation and shame [94]. Sometimes the relationship towards the abusing father was better than that towards a neglecting mother, so that patients should always be allowed to choose, whether they prefer a woman or a man as a therapist [84].…”
Section: Prevention Of Obstetrical Complications Resulting From Csamentioning
confidence: 99%
“…So far, individual therapy and group therapy seem to lead to fewer symptoms and better psychosocial functioning [93]. Psychotherapy groups have often been recommended to reduce the victim's feelings of isolation and shame [94]. Sometimes the relationship towards the abusing father was better than that towards a neglecting mother, so that patients should always be allowed to choose, whether they prefer a woman or a man as a therapist [84].…”
Section: Prevention Of Obstetrical Complications Resulting From Csamentioning
confidence: 99%
“…In contrast to other long-term group therapy interventions, which also focused on the change from an insecure to a secure attachment style [18], [26], a change of a patient’s attachment style is unlikely, as we considered only twelve sessions. Thus the patients will have considered the therapist only in part as a secure basis [15].…”
Section: Discussionmentioning
confidence: 99%
“…Research on the way in which different attachment styles can affect various psychotherapeutic interventions is increasing steadily [17], [24], [25], [26], [27], [28]. Strauss [29] suggests a sensibility in relating the findings of attachment theory to the observations made in a psychotherapeutic interaction, particularly the therapeutic relationship as it can resemble the relationship to an attachment figure.…”
Section: Introductionmentioning
confidence: 99%
“…Dutton (1992b) reported that this emotional connection is rooted during the early phase of the relationship, often before the abuse begins. Intermittent expressions of concern/reinforcement and violence intensify the attachment/traumatic bonding (Barnett, 2001;Saunders & Edelson, 1999). With increasing forced isolation, a dependency on the batterer grows, reducing the potential for constructive change and leaving the relationship.…”
Section: Precontemplationmentioning
confidence: 99%